2022
DOI: 10.1177/08862605211067005
|View full text |Cite
|
Sign up to set email alerts
|

A Latent Class Approach to Understanding Associations between Sports Participation, Substance Use, Dismissive Attitudes, and Sexual Violence Perpetration among High School Athletes

Abstract: Sexual violence (SV) among adolescents continues to be a major public health concern with numerous consequences. Research, predominantly with male collegiate samples, has suggested an association between sports participation and SV perpetration, and has included other important risk factors such as substance use and attitudes. However, more research is needed in this area among adolescents. The current study uses latent class analysis (LCA) to examine data- driven classes of high school student athletes (N = 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…The link between aggression, violence, and substance use is complex (e.g., see Ingram et al, 2022; Katerndahl et al, 2021), and there are several mediating factors. First of all, a meta-meta-analysis showed that there is a positive relationship between substance use and violence (Duke et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The link between aggression, violence, and substance use is complex (e.g., see Ingram et al, 2022; Katerndahl et al, 2021), and there are several mediating factors. First of all, a meta-meta-analysis showed that there is a positive relationship between substance use and violence (Duke et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The sports participation-SV link is also demonstrated through the pervasive use of violent language to describe winning a competition (e.g., "raping" the opponent), objectification of women, and using queerness to signify weakness (Adams et al, 2010;Reigeluth & Addis, 2021;Young et al, 2017). This atmosphere of violence suggests athletes, particularly male athletes, on contact sport teams would be more likely than other athletes or non-athletes to perpetrate SV, which is supported in the few existing studies examining sport contact level (Basile et al, 2020;Ingram et al, 2022). Less is known about girls' and non-binary genders' sports involvement and SV perpetration, and theoretical frameworks to explain it.…”
Section: Np1692mentioning
confidence: 87%
“…Furthermore, research suggests that substance use, particularly alcohol, is associated with SV perpetration (Basile et al, 2018;Tharp et al, 2013) and sports participation (Kwan et al, 2014). Ingram et al 2022 found that U. S. high school athletes who engaged in more than one type of substance use were more likely than their non-substance using peer-athletes to report perpetrating SV, regardless of the type of sport.…”
Section: Attitudes and Behaviorsmentioning
confidence: 99%
“…The empirical papers that follow identify critical risk factors that can serve as important prevention program targets. Ingram and her colleague’s (Ingram et al, 2022) paper explores sexual harassment and violence perpetration with high school athletes and identifies substance use as a major risk factor for perpetration among both females and males. For males in their study, contact-sport participation and attitudes dismissive of SV were found to be associated with perpetration.…”
mentioning
confidence: 99%